Estetyka strony internetowej = Aesthetics of the website - Topolnicka, Elwira (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of the article is to draw attention to the impact of technology in building an aesthetic website. By juxtaposing the rules used for the editorial composition, such as font and it`s size, line length, tracking, kerning and inter-word spacing, the possibilities and limitations in applying the same rules when building texts on websites were demonstrated.
Keywords: internet; strony internetowe; komunikacja internetowa; język nowych mediów; websites; Internet communication; language of new media